Total polyphenols analysis of mature seeds and Tissue cultures of some Colombian cocoa varieties (2008)
ABSTRACT: The aim of this research was to establish cocoa (Theobroma cacao) cell suspensions culture to analyze the total polyphenols content for two colombian cocoa varieties and to compare the results with the total polyphenols content from the same field varieties. The final results showed that it is possible to produce big amount of cocoa cell biomass able to synthesize the metabolites without loosing its organoleptic properties (smell, color, and flavor), and to produce an acceptable content of total polyphenols compared with the natural seeds. this preliminary study is a promising perspective for future production of the antioxidants and to supplement with them the cocoa by-products.